Development of a 3D-printed spongy electrode design for microbial fuel cell (MFC) using gyroid lattice - Pamintuan, Kristopher Ray Simbulan; Manga, Harold Octavo; Balmes, Aprilyn (International Journal of Renewable Energy Development, 2024)
Microbial fuel cell technology addresses both issues in finding new ways to clean water systems while harnessing electricity. Several studies suggest that a single large-scale MFC is proven to be inefficient and expensive. Therefore, producing small-scale MFCs is focused on investigation to provide an efficient system and cost-effective approach. This study used 3D-printed MFCs using a spongy electrode design to produce a modern approach to modifying electrode capacity in energy generation. Furthermore, the study identifies the electrical conductivity of the spongy electrode by determining the voltage generated and power density by stacked MFCs in series, parallel, and hybrid configurations. The MFCs generate a maximum voltage of 633 mV and a current of 14.22 . One way to reduce the effects of voltage reversal in the MFC system is the application of hybrid connection circuits. Parallel-series hybrid connection possesses stable voltage generation of 250−300 ???????? with the highest current generation of 115.20 ????????. At the same time, the Series-Parallel Connection generates the highest voltage and current of 259 mV and 30 , respectively. The spongy electrode design and hybrid connection produced a maximum power and current density of 29.30 μW⁄m2 and 279.41 μA⁄m2 obtained from a different connection of pure parallel and 28P-2S hybrid connection. Furthermore, water quality parameters were examined (pH, TDS, ORP, and COD), that the MFCs design is efficient in wastewater treatment, with a %COD removal of 95.24% efficiency, reduced ORP from +48.00 mV to -7.00 mV, and the TDS concentration from 270 ppm to 239 ppm.